2017
DOI: 10.3747/co.24.3486
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Metronomic Vinorelbine in Elderly Patients with Advanced Non-Small-Cell Lung Cancer and Poor Performance Status

Abstract: Background Metronomic chemotherapy-administration of low-dose chemotherapy-allows for a prolonged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Lung cancer is the leading cause of cancer‐related deaths both in China and worldwide . Almost 80% of these patients have distant metastases when they are diagnosed, so they are not candidates for curative surgery . Epidermal growth factor receptor (EGFR) can be detected in 10% to 15% of white patients and in 40% to 50% of Asian patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is the leading cause of cancer‐related deaths both in China and worldwide . Almost 80% of these patients have distant metastases when they are diagnosed, so they are not candidates for curative surgery . Epidermal growth factor receptor (EGFR) can be detected in 10% to 15% of white patients and in 40% to 50% of Asian patients .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Almost 80% of these patients have distant metastases when they are diagnosed, so they are not candidates for curative surgery. 3 Epidermal growth factor receptor (EGFR) can be detected in 10% to 15% of white patients and in 40% to 50% of Asian patients. 4,5 Several prospective and phase 3 clinical trials have reported that patients with a sensitive EGFR mutation have an objective response rate (ORR) of 70% to 80% with a median progression-free survival (PFS) of approximately 10 months.…”
Section: Introductionmentioning
confidence: 99%
“…Of other toxicities reported, including diarrhea, nausea and vomiting, these are seldom severe and usually respond to treatment ( Depierre et al, 2001 ; Gregory and Smith, 2000 ). Additionally, metronomic vinorelbine (dense, nonbreak, low dose administration) is safely used and well tolerated, with some instances of treatment continuing for over 3 years without overt toxicity ( Briasoulis et al, 2009 ; Camerini et al, 2015 ; Bilir et al, 2017 ). Furthermore, one report of 62 patients treated with metronomic vinorelbine (20–70 mg thrice weekly) reported non-hematological toxicities to be practically absent, describing vomiting and nausea as negligible ( Briasoulis et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metronomic approach is considered intriguing due to its anti-angiogenic effect and the possible synergy with molecularly-targeted agents and immune checkpoints inhibitors [ 12 14 ]. Moreover, lack of major side-effects while preserving anti-neoplastic activity makes this schedule highly attractive for the management of heavily pretreated patients or elderly/frail ones [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%